The characteristics of community seed schemes for grains and legumes: Insights from northern Nigeria - Takeshima, Hiroyuki; Ragasa, Catherine; Bamiwuye, Temilolu; Andam, Kwaw S.; Spielman, David J.; Omoigui, Lucky (Elsevier, 2025)
CONTEXT Despite the significant roles that intermediary seed systems play in the supply of quality seed in developing countries, including Africa South of the Sahara, the knowledge gap remains generally substantial regarding the general characteristics and seed quality assurance performance of intermediary seed systems like community seed schemes (CSS), which still predominantly operate outside the formal seed systems.